UMPSA strengthens global ties with Mohamed Bin Zayed University for humanities through strategic partnership - Nur Ezzati, Mohd Nasir (UMPSA, 2024)
ABU DHABI, 3 October 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has further expanded its global presence by formalising a Memorandum of Understanding (MoU) with Mohamed bin Zayed University for Humanities (MBZUH).